International organizations : principles and issues - Bennett, A. LeRoy, 1914- (Alvin LeRoy) (Prentice Hall, 2002)
For upper-level undergraduate and graduate-level courses dealing with International Organizations, the United Nations, and the UN System. This comprehensive, historical, institutional, and functional/programmatic analysis of the development of contemporar